## THIS USER ASKED ๐

**Identify the error in the student solution shown below. find the correct answer. show how you got your answer. i am struggling to understand 2in(x) = in3(x) – [ in(9) – 2in(3) ] in(x^2) = in(3x) – [ in(9) – in(9) ] in(x^2) = in(3x) – 0 in(x^2) = in(3x/0); division by 0, undefined**

## THIS IS THE BEST ANSWER ๐

Since 0 in ln (3x) – 0 is not logarithm, logarithm property cannot be used here. The difference shown cannot be written as a logarithm quotient. The phase ln (x2) = ln (3x) – (0) decreases to

ln (x2) = ln (3x). Possible solutions are 0 and 3, and 0 is missing.

## Leave a Reply